Influence of seed ageing on growth and yield of soybean - Saha, Rina Rani; Sultana, Wahida (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Effect of seed ageing on stand establishment, growth and yield of three soybean varieties was studied. Treatments consisted of three varieties viz. Shohag, Bangladesh soybean 4 and BARIsoybean-5 with four levels of seed ageing viz. 20, 12, 8 and 2 months aged seed. Seed germination and field emergence percentage decreased but electrical conductivity of seed leachate increased with increasing seed age in all the soybean varieties. Irrespective of varieties, plants grown from 20 months aged seed accumulated more dry matter per plant but crop growth rate (CGR) were lower than the other ageing treatments. The highest dry matter accumulation and CGR were found in BARIsoybean-5 and lowest in Bangladesh soybean 4. Irrespective of varieties, crop grown from 2 months aged seed produced significantly the highest seed yield (1981 kg/ha) which was at par with the yield obtained from 8 months aged seed; and the lowest (811 kg/ha) was grown from 20 months aged seed. Among the varieties, significantly the highest seed yield (1615 kg/ha) was obtained from BARIsoybean-5 which was identical with that of Bangladesh soybean 4. Results further revealed that Bangladesh soybean 4 can be grown up to 12 months aged seed without significant reduction in seed yield. Â Key words: Seed ageing, Stand establishment, Crop growth rate, Seed yield doi:10.3329/bjb.v37i1.1559 Bangladesh J. Bot. 37(1): 21-26, 2008 (June)